2004
DOI: 10.1113/jphysiol.2004.061184
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cAMP and β‐adrenergic stimulation recruits CaV3 T‐type channels in rat chromaffin cells through Epac cAMP‐receptor proteins

Abstract: T-type channels are expressed weakly or not at all in adult rat chromaffin cells (RCCs) and there is contrasting evidence as to whether they play a functional role in catecholamine secretion. Here we show that 3-5 days after application of pCPT-cAMP, most RCCs grown in serum-free medium expressed a high density of low-voltage-activated T-type channels without altering the expression and characteristics of high-voltage-activated channels. The density of cAMP-recruited T-type channels increased with time and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
85
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 65 publications
12
85
0
1
Order By: Relevance
“…As reported by various groups, T-type channels are either absent or weakly expressed in bovine and rat chromaffin cells (RCCs) [15,23,24,31] but can be expressed when RCCs are exposed to cAMP for several days [25,49], after overnight incubation in hypoxic conditions (3% O 2 ) or in the presence of the hypoxia mimicking factor deferoxamine (DFX) ( Fig. 1; see also [9] and [19]).…”
Section: T-type Channels and Fast Capacitance Changes In Rat Melanotrmentioning
confidence: 81%
See 4 more Smart Citations
“…As reported by various groups, T-type channels are either absent or weakly expressed in bovine and rat chromaffin cells (RCCs) [15,23,24,31] but can be expressed when RCCs are exposed to cAMP for several days [25,49], after overnight incubation in hypoxic conditions (3% O 2 ) or in the presence of the hypoxia mimicking factor deferoxamine (DFX) ( Fig. 1; see also [9] and [19]).…”
Section: T-type Channels and Fast Capacitance Changes In Rat Melanotrmentioning
confidence: 81%
“…Thus, exposure to cAMP, chronic hypoxia, and β 1 -adrenergic stimulations (which raise the level of cAMP) appear to be the suitable factors for mimicking prolonged stress conditions in vitro. We found that all these factors induce a common response in RCCs: a marked recruitment of α 1H T-type channels through cAMPreceptor proteins (Epac) [49]. This lowers the threshold of cell excitability and increases the quantity of catecholamine secreted near resting potentials [25].…”
Section: T-type Channels and Fast Capacitance Changes In Rat Melanotrmentioning
confidence: 99%
See 3 more Smart Citations